A Moorean argument for the full moral status of those with profound intellectual disability. Issue 1 (15th December 2015) - Curtis, Benjamin; Vehmas, Simo
Abstract : This paper is about the moral status of those human beings who have profound intellectual disabilities (PIDs). We hold the common sense view that they have equal status to 'normal' human beings, and a higher status than any non-human animal. On the standard account of moral status, this view cannot be sustained. In this paper, we ask whether, in order to be justified in continuing to hold our view, we are obliged to offer an alternative account that does sustain it? Our answer is that we are not.